Exploring urine biomarkers of early health effects for occupational exposure to titanium dioxide nanoparticles using metabolomics. Issue 7 (11th February 2021) - Chen, Zhangjian; Han, Shuo; Zhang, Jiahe; Zheng, Pai; Liu, Xiaodong; Zhang, Yuanyuan; Jia, Guang
Abstract : The present study found that urine metabolites represented by dibenzyl ether are good biomarkers of early health effects for occupational exposure to TiO2 nanoparticles. Abstract : Many experimental studies have demonstrated that titanium dioxide nanoparticles (TiO2 NPs) could induce adverse health effects in vivo and in vitro . But epidemiological evidence and biomarkers related to early health effects are still lacking. This study aimed to explore biomarkers in the urine samples of workers occupationally exposed to a relatively low concentration of TiO2 NPs. A cross-sectional study was conducted in Jinan, China, involving 132 employees of a TiO2 NP manufacturing plant, among which the exposed group and control group were 1 : 1 matched by confounding factors such as gender, age, BMI, smoking and drinking. Untargeted metabolomics was performed in urine samples using high performance liquid chromatography-mass spectrometry (HPLC-MS) technology. The differential metabolites between the TiO2 NP exposed group and the control group were analyzed and then screened for potential biomarkers using bioinformatics methods. Metabolomics found a total of 1760 differentially expressed metabolites in the TiO2 NP exposed group, of which 60 differential metabolites were simultaneously confirmed by one-dimensional and multi-dimensional statistical analysis. Among these 60 differential metabolites, the relative expression of 27 metabolites increased, and the remaining 33 decreased. Pathway enrichment analysis further found that the metabolic pathway of long chain acyl-coa dehydrogenase deficiency (Lcad) was significantly enriched. Ten differential metabolites were selected as potential biomarkers of occupational exposure to TiO2 NPs using machine learning methods, including dibenzyl ether, quassimarin, tryptophan, etc . The receiver operating characteristic curves (ROCs) of these potential biomarkers showed good sensitivity and specificity. These potential biomarkers also had biological basis for occupational exposure to TiO2 NPs. Therefore, urine metabolites represented by dibenzyl ether are considered as good biomarkers of early health effects for occupational exposure to TiO2 NPs.